2014
DOI: 10.1080/09602011.2014.973886
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of face-processing skills in an adolescent with prosopagnosia: Evaluation of an online perceptual training programme

Abstract: In this paper we describe the case of EM: a female adolescent who acquired prosopagnosia following encephalitis at the age of eight. Initial neuropsychological and eye-movement investigations indicated that EM had profound difficulties in face perception as well as face recognition. EM underwent 14 weeks of perceptual training in an online programme that attempted to improve her ability to make fine-grained discriminations between faces.Following training, EM's face perception skills had improved, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 63 publications
(80 reference statements)
3
30
0
Order By: Relevance
“…The additional eight articles appeared to be in line with the outcome of the literature reviews, especially with regard to transferring the training to real-life face recognition (Bate et al, 2015). The study by Davies- Thompson et al (2017) describes a promising restorative approach, however training is very intense and does not improve real-life facial recognition in all participants involved.…”
Section: Prosopagnosia and Object Agnosiasupporting
confidence: 57%
“…The additional eight articles appeared to be in line with the outcome of the literature reviews, especially with regard to transferring the training to real-life face recognition (Bate et al, 2015). The study by Davies- Thompson et al (2017) describes a promising restorative approach, however training is very intense and does not improve real-life facial recognition in all participants involved.…”
Section: Prosopagnosia and Object Agnosiasupporting
confidence: 57%
“…Davies-Thompson et al (2017) reported an average ~10% improvement in CFMT scores in 10 adults with acquired prosopagnosia, but this was not significant in a group-level analysis. Although CFMT gains were not available in the studies reported by colleagues (2007, 2014), Bate et al (2015) did not detect an improvement on this test for their adolescent case with acquired prosopagnosia. Whether the larger gains reported here result from the training strategy itself (i.e.…”
Section: Discussionmentioning
confidence: 76%
“…Twelve manipulated images were then created from each base image, using different combinations of four adjustments (see Figure 2A and 2B): two affecting the spacing of facial features (the distance between the eyes, or the distance between the eyes and mouth), and two affected the size of specific facial features (the eyes and nose). These manipulations were taken from the design of existing training programmes that have experienced at least some success: expression was manipulated by Davies-Thompson et al (2017), spacing by DeGutis et al (2007DeGutis et al ( , 2014, and FACIAL IDENTITY TRAINING 11 feature size by Bate et al (2015). Together, a total of 24 new character images were created for each of the male and female insert cards.…”
Section: < Insert Figure 1 >mentioning
confidence: 99%
“…The last 20 years has seen an abundance of interest in individuals with developmental prosopagnosia (DP), with increasing numbers of adults and children self-referring for clinical screening and/or research participation (e.g. Bate & Bennetts, 2015;Bennetts, Murray, Boyce & Bate, 2017;Bowles et al, 2009;Dalrymple & Palermo, 2015;Geskin & Behrmann, 2017).…”
Section: Prosopagnosia Severitymentioning
confidence: 99%